THE RELATIONSHIP BETWEEN LEADERSHIP STYLE AND ORGANIZATIONAL COMMUNICATION ON EMPLOYEE PERFORMANCE - Claudia, Rosalita; Tampubolon, Emma; Sunaryo, Tarsicius (Universitas Kristen Indonesia, 2021)
This research aims to determine how the relationship between leadership style and organizational communication on employee performance at Pondok Kelapa coffee shop. The data used in this study are secondary data in the form of primary data and secondary data. Primary data used by providing a list of questions (questionnaire) to respondents and secondary data through journals that support this research. The data analysis method used is non-parametric statistics using SPSS (Statistical Package for Social Sciences) software which can be used in social research. The hypothesis used is the Spearman Rank correlation analysis statistical technique. Based on the results of data analysis, there is no significant relationship between leadership style and employee performance of Kopiyor Pondok Kelapa as indicated by the value of tcount (1.760) <ttable (2.160). There is a significant relationship between organizational communication and employee performance of Kopiyor Pondok Kelapa which is indicated by the value of t (3.267) <t table (2.160). The author's suggestions regarding the leadership style of the leader must be able to provide motivation when employees work and continue to improve in providing direction to employees so that employee performance increases. Regarding organizational communication, the leader must be able to properly accept any complaints while working and regarding the performance of employees, employees must be able to make decisions on minor problems, fellow employees must help each other in completing tasks. Keywords:leadership style, organizational communication and employee performance.